The Inhibitory Effect of Clomipramine on Intestinal Motility in Female Rats - Sayin, O.; Oz, Z. D.; Pervin, M.; Bozyil, A. S.; Batmaz, H.; Serhatlioglu, I.; Kacar, E. (Wiley, 2025)
[Abstract Not Available]